Impacts of dysphagia on the quality of life of patients with Parkinson's disease (Research, Society and Development, 2020)
Dysphagia is a clinical symptom present in Parkinson's disease, which contributes negatively to the patient's health status, leading to loss of pleasure when eating, influencing aspects of morbidity, mortality and quality of life. The present study aimed to identify the impacts caused by dysphagia, on the quality of life of patients with Parkinson's disease. This is a literature review, searching for articles in the following databases: electronic Scientific Eletronic Library Online (SCIELO), Latin American Caribbean Literature in Public Health (LILACS), US National Library of Medicine (PUBMED) between the years 2010 to 2020. The patient with Parkinson's disease who presents with dysphagia can manifest several changes in the swallowing action, among them, salivation problem, inability to handle food, difficulty with food in the mouth, choking, sudden contraction before, during and after swallowing, leading to involuntary weight loss, impaired health and quality of life. From this perspective, multidisciplinary monitoring is essential, helping patients to preserve their health and improve their quality of life. With this study it was possible to know the impacts of dysphagia on the quality of life of patients with Parkinson's disease. The need for further studies on the impacts caused by dysphagia is noteworthy, since, currently, the number of people with Parkinson's Disease has been growing significantly, and when associated with dysphagia, they have a greater impact on the quality of life of its patients.